DSG2 expression is low in colon cancer and correlates with poor survival - Tingting Yang (BMC Gastroenterology, 2021)
Abstract Background Desmoglein2 (DSG2) is a transmembrane protein that helps regulate intercellular connections and contributes to desmosome assembly. Desmosome are associated with cell adhesion junctions, which play an important role in cancer progression specially cancer cell migration and invasion. However, DSG2 expression in colon cancer (CC) and its association with CC patients’ overall survival (OS) are still unclear. Methods We collected 587 CC samples, 41 colitis tissues and 114 pericarcinomatous tissues, as well as corresponding clinicopathological data about the patients who contributed them. All samples were tested immunohistochemically in tissue microarrays. Kaplan–Meier method was used for calculating patient survival. Univariate and multivariate analyses was used for investigating DGS2 link with CC patient’s clinicopathological factors. Bioinformatics analysis was also used in study. Results The results showed that DSG2 expression was lower in CC tissues than in pericarcinomatous tissues (P < 0.001). DSG2 expression was associated with differentiation (P = 0.033), lymph node metastasis (P = 0.045), distant metastasis (P = 0.006) and AJCC stage (P < 0.001). Univariate analysis indicated that poor OS in patients with CC was associated with low DSG2 expression (P < 0.001), tumor size (P < 0.001), lymph node metastasis (P < 0.001), distant metastasis (P < 0.001), AJCC stage (P < 0.001) and venous invasion (P < 0.001). In multivariate analysis, low DSG2 expression (P < 0.001), distant metastasis (P < 0.001), AJCC stage (P = 0.002), venous invasion (P < 0.001) were independent prognostic factors for CC patients. Bioinformatics analysis indicated that low DSG2 expression affects protein activation, regulates the P53-related pathway in CC, and activates the EGFR pathway. Conclusions The results suggest that low DSG2 expression is associated with poor survival for CC patients. DSG2 could be a prognostic biomarker for CC.